A SIX-MONTH STUDY OF CLINICAL SYMPTOMS, IMAGING AND OUTCOMES OF PATIENTS DIAGNOSED WITH CEREBRAL VENOUS SINUS THROMBOSIS (CVST) - Ardalani, Ghasem Fatahzadeh; Pourfarzi, Farhad; Haddad, Amir (MNJ (Malang Neurology Journal), 2024)
Background: One of the unusual cause of headache and stroke is CVST with very diverse clinical manifestation. Onset of focal headache, headache with seizures, papilledema, or focal defect are some of important clinical features. Consideration of risk factors, especially the use of hormonal drugs, recent pregnancy, coagulation disorders, as well as recent infections and systemic inflammation, can lead to clinical suspicion of CVST. For early and accurate detection we can use modern MR imaging. Objective: To evaluate the clinical symptoms and imaging findings of patients with a diagnosis of CVST during 6-months follow-up. Methods: This cross-sectional study was used on 56 patients with CVST. Clinical, preclinical, and imaging records of inpatients and also information like age, sex, and underlying diseases were collected at a checklist.  After 6 months from the start of treatment, the identified patients were followed up through a telephone interview, and if there were any positive symptoms, they were visited on an outpatient basis in the neurology clinic of Alavi Hospital in Ardabil, and the necessary information was extracted. Collected data were analyzed by statistical methods in SPSS version 21. Results: Of all patients, 47 (84%) were women. The most common symptom was headache with 87.5% and then nausea and vomiting, sensory and visual symptoms with 57.1%, 51.8% and 44.6%, respectively. Conclusion: The results of this study showed that, the clinical symptoms of patients are very various and misleading, but the most common clinical symptoms were headache, nausea and vomiting. Women were involved more than men. The results of the study disclosed that CVST had wide range of clinical manifestations and non-specific symptoms at the beginning. For that reason, in especially high risk groups for thrombosis, the diagnosis of CVST should be kept in mind.